Productivity and Technological Change in the Bituminous Coal Industry, 1919-54 - Maddala, G. S. (Journal of Political Economy, 1965)
Study fits Cobb-Douglas production function to the bituminous coal industry. Author concludes that increase in productivity is due almost entirely to increase in horsepower per worker, with residual due to work force quality changes.